The Relationship of Performance Appraisal with Organizational Commitment of Employees (The Case of OYA and COB Administrative Staff in UUM) - Mohamed, Fatima Abdullahi (2012)
This study investigates the relationship of performance appraisal with organizational commitment of administrative employees of Othman Yeop Abdullah Graduate School of Business and College of Business, University Utara Malaysia. Thirty questionnaires were returned to which ANOVA one way test was used to verify the demographic profiles of the participants with organizational commitment. The result found that 45% of administrative employees of OYA and COB have lower level of organizational commitment. Pearson correlation was conducted on the independent variable which is (HRM practice of performance appraisal), dependent variable (organizational commitment) and mediating variable (perceived organizational support). This study revealed that there is moderate non-directional neither positive nor negative correlation between performance appraisal with organizational commitment of employees, performance appraisal with perceived organizational support and between organizational commitment with perceived organizational support. The result of the study contributed to a need for developing adequate training programs and offer opportunity for academic programs which aims on improving the knowledge and skills of the employees.